Integration of Spirituality in Medical Education in Iran: A Qualitative Exploration of Requirements. (24th November 2015) - Memaryan, Nadereh; Rassouli, Maryam; Nahardani, Seyedeh Zahra; Amiri, Parisa
Abstract : Background . Healthcare system has needed to provide spiritual services, and one of the reasons for not addressing spirituality in this field is lack of training in this area. This study purpose is to explore and identify main requirements for designing this education, in Iran. Materials and Methods . This is a qualitative study with conventional content analysis method. 18 participants, who were main stakeholders in spirituality, medical education, and curriculum development, were selected by purposive sampling. Data were collected using semistructured interviews, which continued until data saturation. Results . Three main themes and their categories were extracted from analysis of data. The themes are (1) educational needs including clinical practice needs; (2) opportunities including rich background and backup, perceived clinical need, and right context of medical education for change; and (3) challenges including challenges in academic planning and barriers to implementation. Conclusion . All stakeholders acknowledged the need for addressing spirituality in formal medical education. It seems that implementation of such programs requires attention to facilitating factors and challenges proposed by those involved.